STUDI DAERAH PENANGKAPAN IKAN DI PERAIRAN SUNGAI KAMPAR KANAN DESA KAMPUNG PANJANG KECAMATAN KAMPAR TIMUR KABUPATEN KAMPAR PROVINSI RIAU - Putri Ana Pratiwi; Alit Hindri Yani; Nofrizal ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted on 9 May 2015 in Kampar Kanan river, Kampung Panjang village, Kampar Timur District, Kampar regency, province of Riau. Purpose of this study was to obtain data on environmental parameters become the benchmark fishing grounds and fishing activity there. Environmental parameters measured are temperature, current speed, brightness, depth and acidity (pH). After doing this research is that the condition of the Kampar Kanan river Kampung Panjang Village still quite good and still support for life of organisms that were in it and deserves to fishing activities in these waters.Keyword : fishing ground, environmental parameters, Kampar Kanan river